Understanding Magnetic Resonance Imaging in Multiple Sclerosis (UMIMS): Development and Piloting of an Online Education Program About Magnetic Resonance Imaging for People With Multiple Sclerosis - Freund, Magalie; Schiffmann, Insa; Rahn, Anne Christin; Chard, Declan; Lukas, Carsten; Scheiderbauer, Jutta; Sippel, Anna; Heesen, Christoph (Frontiers in Neurology, 2022)
Background: People with multiple sclerosis (pwMS) lack sufficient magnetic resonance imaging (MRI) knowledge to truly participate in frequently occurring MRI related therapy decisions. An evidence-based patient information (EBPI) about MRI is currently lacking. Objective: The aim of this study was to develop an evidence-based online education program about limitations and benefits of MRI for pwMS. Ultimately, our goal was to improve MRI risk-knowledge, empower pwMS and promote shared decision-making. Methods: The program’s contents were based on literature research and a previous pilot study. It was revised following 2 evaluation rounds with pwMS, MRI experts and expert patients. In a pilot study n=92 pwMS received access to the program for 4 weeks. User experiences and acceptance, MRI knowledge (MRI-RIKNO 2.0 questionnaire) and emotions and attitudes towards MRI (MRI-EMA questionnaire) were assessed. Results were compared to a previous survey population of n=508 pwMS without access to the program. Results: Participants rated the program as easy to understand, interesting, relevant, recommendable and encouraging. In comparison to pwMS without access to the program, MRI risk-knowledge and perceived MRI competence was higher. Conclusion: Satisfaction with the program and good MRI-risk knowledge after usage demonstrate the need and applicability of EBPI about MRI in MS.